1982
DOI: 10.1021/je00029a041
|View full text |Cite
|
Sign up to set email alerts
|

Fusion properties and heat capacities of the eutectic lithium fluoride-sodium fluoride-potassium fluoride melt

Abstract: The fusion properties (melting point, enthalpy and entropy of fusion) of the eutectic LIF-NaF-KF and the heat capacity of this system In the poly crystalline state and In the molten state have been Investigated by the technique of hlgh-temperature differential scanning calorimetry. The fusion properties and heat capacities may be summarized as follows: mp 462 ± 2 °C; = 3.98 kcal mol"1; AS*. -5.42 eu; C.(soHd) -12.8218 -(9.851 X 10"3)f + (1.513 X 10-*)?•* and Cp(meK) = 9.8380 + (10.487 X 10"3) , both In cal mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
26
1

Year Published

1982
1982
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 0 publications
10
26
1
Order By: Relevance
“…The results of the subsequent experiments with the same sample did not differ. After the third reading the position of the melting peak remained unchanged, and its maximum corresponded to the melting temperature of the eutectic reported in [18]. The melting enthalpy measured equal to 385 ± 12 J/g is in agreement with the results obtained previously.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the subsequent experiments with the same sample did not differ. After the third reading the position of the melting peak remained unchanged, and its maximum corresponded to the melting temperature of the eutectic reported in [18]. The melting enthalpy measured equal to 385 ± 12 J/g is in agreement with the results obtained previously.…”
Section: Resultssupporting
confidence: 91%
“…As noted in [18], the melting temperature of eutectic LiF-NaF-KF mixture decreased in subsequent repeated measurements. This decrease can be due to a slow homogenization of the salt melt (the highest experimental temperature was 1133 K, whereas the melting points for the mixture components are 1121, 1261, and 1129 K for LiF, NaF, and KF, respectively).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The specific heat capacity of FLiNaK molten salt has been experimentally and theoretically studied [23][24][25][26], as summarized in Fig. 4, suggesting the specific heat capacity obtained in this work is very close to the extensively accepted value of 1.88 J/g K [2,4,5,23,27].…”
Section: Specific Heat Capacity Of Flinak Molten Saltsupporting
confidence: 74%
“…The available value from the ORNL in 1950s was 4.5 W/(m K) using a self-developed variable gap device, and the experimental error was less than 25% [31], however, this result was verified to be far away from the real values during the calculation for system design in MSRE project. Smirnov et al [32] measured the thermal conductivity of the FLiNaK molten salt by the method of coaxial cylinders and the values located in the range from 0.80 to 0.95 W/(m K) in the temperature range of 800-1100 K with the accuracy less than 4%, and it was reported to be 0.82-0.96 W/(m K) in 800-1100 K recently [25]. Serrano-López et al [27] suggested the thermal conductivity of the FLiNaK molten salt was a constant of 0.85 W/(m K), but the deviation was 0.206 W/(m K).…”
Section: Thermal Conductivity Of Flinak Molten Saltmentioning
confidence: 99%